Peran Lingkungan terhadap Optimalisasi Perkembangan Bahasa Anak Usia Dini - Alfu Laila, Noor (Jurnal Muadalah, 2013)
Children in their early childhood have their own world and charecteristic which are different from the adultâs. One of the difference is their language. Through the medium of language, a child is able to build his/her communication with other people (social skill). This situation can be achieved if the education principals of the children have been fulfilled and focused thoroughly. It is essential for parents and educators to comprehend their childrenâs golden age and to know further about the language development which their children should have in accordance with its steps.Keywords: children of early age, language, parents/educators, golden age, developmentAnak usia dini memiliki dunia dan karakteristik sendiri yang jauh berbeda dari orang dewasa. Salah satunya melalui berbahasa, seseorang atau anak akan dapat mengembangkan kemampuan bergaul (social skill) dengan orang lain. Hal ini dapat tercapai jika prinsip-prinsip pendidikan anak usia dini dipenuhi dan diperhatikan dengan seksama. Perlu bagi orang tua maupun pendidik untuk memahami masa golden agenya anak-anak dan mengetahui lebih jauh tentang perkembangan bahasa yang seyogyanya sudah dimiliki anak sesuai dengan tahapan-tahapan mereka.Kata kunci: anak usia dini, bahasa, orangtua/pendidik, masa keemasan, perkembangan.